Comparative analysis of the phytocyanin gene family in 10 plant species: a focus on Zea mays - Cao, Jun; Li, Xiang; Lv, Yueqing; Ding, Lina (Frontiers in Plant Science, 2015)
Phytocyanins (PCs) are plant-specific blue copper proteins, which play essential roles in electron transport. While the origin and expansion of this gene family is not well investigated in plants. Here, we investigated their evolution by undertaking a genome-wide identification and comparison in 10 plants: Arabidopsis, rice, poplar, tomato, soybean, grape, maize, Selaginella moellendorffii, Physcomitrella patens and Chlamydomonas reinhardtii. We found an expansion process of this gene family in evolution. Except PCs in Arabidopsis and rice, which have described in previous researches, a structural analysis of PCs in other eight plants indicated that 292 PCs contained N-terminal secretion signals and 217 PCs were expected to have glycosylphosphatidylinositol-anchor signals. Moreover, 281 PCs had putative arabinogalactan glycomodules and might be AGPs. Chromosomal distribution and duplication patterns indicated that tandem and segmental duplication played dominant roles for the expansion of PC genes. In addition, gene organization and motif compositions are highly conserved in each clade. Furthermore, expression profiles of maize PC genes revealed diversity in various stages of development. Moreover, all nine detected maize PC genes (ZmUC10, ZmUC16, ZmUC19, ZmSC2, ZmUC21, ZmENODL10, ZmUC22, ZmENODL13, and ZmENODL15) were down-regulated under salt treatment, and five PCs (ZmUC19, ZmSC2, ZmENODL10, ZmUC22, and ZmENODL13) were down-regulated under drought treatment. ZmUC16 was strongly expressed after drought treatment. This study will provide a basis for future understanding the characterization of this family.